2004
DOI: 10.1074/jbc.m303697200
|View full text |Cite
|
Sign up to set email alerts
|

Flexible N-terminal Region of Prion Protein Influences Conformation of Protease-resistant Prion Protein Isoforms Associated with Cross-species Scrapie Infection in Vivo and in Vitro

Abstract: Transmissible spongiform encephalopathy (TSE) diseases are characterized by the accumulation in brain of an abnormal protease-resistant form of the host-encoded prion protein (PrP), PrP-res. PrP-res conformation differs among TSE agents derived from various sources, and these conformational differences are thought to influence the biological characteristics of these agents. In this study, we introduced deletions into the flexible N-terminal region of PrP (residues 34 -124) and investigated the effect of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…Additional studies have also suggested that the N terminus is important in PrP C function and pathogenesis. The N terminus modifies disease phenotype (43) and influences the conformation and generation of PK-resistant PrP Sc (44,45) as well as rPrP aggregation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have also suggested that the N terminus is important in PrP C function and pathogenesis. The N terminus modifies disease phenotype (43) and influences the conformation and generation of PK-resistant PrP Sc (44,45) as well as rPrP aggregation (37).…”
Section: Discussionmentioning
confidence: 99%
“…The construct used in the present work corresponds to the structured 111-residue C-terminal domain of the murine cellular prion protein and lacks the entire flexible N-terminal region, which has been implicated in transmissible spongiform encephalopathy transmission and in the formation of protease-resistant aggregates (21). Moreover, the segment comprising amino acid residues 106 -126 in full-length PrP represents the most conserved and hydrophobic region, is known to form neurotoxic aggregates in vitro, and is generally considered to form the amyloidogenic core of the protein (33).…”
Section: Discussionmentioning
confidence: 99%
“…Ref. 21). The N-terminal domain also contains amino acid sequences that are generally considered important in the control of aggregation (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High pressure liquid chromatography-purified synthetic single-stranded RNA fragment 43-59 of SAF93 aptamer (SAF93 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] ) (22) and opRNA, a random 18-mer sequence, derived from a translational operator of MS2 bacteriophage (37) were obtained from Integrated DNA Technologies, Inc. (Coralville, IA). Nucleotide sequences were: SAF93 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] , 5Ј-GGA UGC AAU CUC CAU CCC-3Ј; and opRNA, 5Ј-AAA CAU GGG UUC CCA UGU-3Ј. Synthetic RNA samples were maintained lyophilized at Ϫ20°C and used in RNase-free water.…”
Section: Methodsmentioning
confidence: 99%